Epididymal epithelium propels early sexual transmission of Zika virus in the absence of interferon signaling - Alexander G. Pletnev (Nature Portfolio, 2021)
Zika virus can be sexually transmitted. Here, Pletnev et al. show in an immunocompromised mouse model that the epithelial cells of the epididymis, rather than cells of the testis, vas deferens, prostate, or seminal vesicles, are the most likely source of male-to-female sexually transmitted ZIKV genomes.